2016
DOI: 10.1111/gwao.12117
|View full text |Cite
|
Sign up to set email alerts
|

‘But It's Your Job To Be Friendly’: Employees Coping With and Contesting Sexual Harassment from Customers in the Service Sector

Abstract: This article analyses how employees in the service sector respond to sexual harassment from customers and attempts to explain why this is so. There are only a small number of previous studies examining the issue of customer-perpetrated sexual harassment. Those that have been conducted have detailed the nature and prevalence of sexual harassment from customers, but this research lags behind employee experience and some emerging policy responses to this issue. The extant literature, whilst growing, remains large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
112
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(131 citation statements)
references
References 67 publications
12
112
0
7
Order By: Relevance
“…These gendered power differentials are further exacerbated by customeremployee power relations, where customers, patrons, clients, and patients hold power over frontline employees. Work in women's and gender studies, as well as social psychology, also explore employees' perceptions of and responses to sexual harassment (e.g., Morganson & Major, 2014;Good & Cooper, 2016).…”
Section: Findings Outside Of Lismentioning
confidence: 99%
See 3 more Smart Citations
“…These gendered power differentials are further exacerbated by customeremployee power relations, where customers, patrons, clients, and patients hold power over frontline employees. Work in women's and gender studies, as well as social psychology, also explore employees' perceptions of and responses to sexual harassment (e.g., Morganson & Major, 2014;Good & Cooper, 2016).…”
Section: Findings Outside Of Lismentioning
confidence: 99%
“…Despite growing calls within LIS for further examination of the issue (Carlton, 2017;Dewitt, 2017;Jensen, 2017;McLain & Civitello, 2017), third-party sexual harassment against library workers is largely ignored and research on this topic is noticeably lacking. Studies in other fields demonstrate that most instances of third-party sexual harassment go unreported, and that employees often feel obligated to react to these occurrences independently, with informal responses and coping strategies (Gettman & Gelfand, 2007;Good & Cooper, 2016;Hughes & Tadic, 1998;Morganson & Major;2014;Vaughn, 2002). The under-reporting and normalcy of this issue in LIS has likely contributed to its lack of acknowledgement in academic and professional scholarship.…”
Section: Findings Within Lismentioning
confidence: 99%
See 2 more Smart Citations
“…Gilbert, Guerrier, and Guy (1998) found that 19 per cent of companies they studied reported that employees had "resigned due to harassment by customers" and a further "23 per cent could not say one way or another if this was a reason" (p. 51). Likewise, Good and Cooper (2016) argue that customer sexual harassment is a "significant issue", and "customers are increasingly being recognized as potential perpetrators of sexual harassment in public policy and legislation" (p. 3). But why is it the case that customer sexual harassment is so common in the hospitality industry?…”
Section: Definition Of Sexual Harassmentmentioning
confidence: 99%